VALUES OF CHARACTER EDUCATION IN LITERARY WORK (A COMPARATIVE STUDY BETWEEN HAMKA’S FALSAFAH HIDUP AND GIBRAN’S THE PROPHET) - Nahdhiyah, Nahdhiyah (Elite : English and Literature Journal, 2017)
Abstract This study aims to find and to compare (similarities and differences) values of character Education in literary works those are Falsafah Hidup by Hamka and The Prophet by Khalil Gibran. This study reveals values of character education beyond a literary work in order to give contribution to build human character. This study also gives information that literary work is not only display a beautiful string of word but it contains life meaning, so literary work can be an alternative source for building human character. This study uses content analysis technique and comparative approach with coding sheet as the instrument.Falsafah Hidupand The Prophet as object of study. Data analysis starts from preparing data, defining unit of analysis, building coding sheet, coding, comparing, making conclusion, and reporting. Result of study shows there are 13 values of char4acter education in Falsafah Hidupand 11 values of character education in The Prophet. There are some same and different in value and both of these works focus on humanistic and social value. But some values in Falsafah Hidup are not found in The Prophet. The value is character toward nation. Values of character education in The Prophet are not refer to certain religion or faith. Differ than Falsafah Hidup, the values always relies on Al Qur’an and Hadits. Abstrak Nilai Pendidikan Karakter pada Karya Sastra. Penelitian ini bertujuan untuk memperoleh dan membandingkan nilai pendidikan karakter pada karya sastra Falsafah Hidup oleh Hamka dan The Prophet oleh Khalil Gibran. Penelitian ini dapat memberikan kontribusi pada pembentukan karakter manusia serta memberikan pengetahuan bahwa karya sastra bukan hanya menampilkan rangkaian kata-kata indah, namun juga makna hidup. Dengan demikian, karya sastra juga berfungsi untuk membangun karakter manusia. Penelitian ini menggunakan, teknik analisis isi dan pendekatan komparatif dengan lembar pengkodean sebagai instrumennya. Falsafah Hidup dan The Prophet sebagai objek penelitian dimana analisis data dimulai dari mempersiapkan data, mendefinisikan, membuat lembar pengkodean, pengkodean, membandingkan, membuat kesimpulan, dan pelaporan. Hasil penelitian menunjukkan ada 13 nilai-nilai pendidikan karakter di Falsafah Hidup dan 11 nilai-nilai pendidikan karakter dalam The Prophet. Kedua karya ini fokus pada nilai humanistik dan sosial, tapi beberapa nilai dalam falsafah Hidup tidak ditemukan dalam The Prophet, yaitu nilai karakter bangsa. Nilai-nilai pendidikan karakter dalam The Prophet tidak mengacu pada agama atau kepercayaan tertentu. Berbeda dari Falsafah Hidup yang nilai-nilainya selalu bergantung pada Al Qur’an dan Hadits.